Antibacterial Peptide HHC-36 Sustained-Release Coating Promotes Antibacterial Property of Percutaneous Implant - Miao, Qiang; Sun, Jin-Long; Huang, Fei; Wang, Jing; Wang, Pei; Zheng, Ya-Fei; Wang, Feng; Ma, Chu-Fan (Frontiers in Bioengineering and Biotechnology, 2021)
Percutaneous implants are widely used in clinical practice. However, infection is the main clinical problem of percutaneous implants. Titanium dioxide nanotubes are suitable for forming coatings on complex surfaces such as implants. HHC-36, a cationic antimicrobial peptide, has been identified to have a strong broad-spectrum antibacterial effect. In the present study, we use poly D,L-lactic acid (PDLLA) and poly lactic-co-glycolic acid (PLGA) coating to build HHC-36 sustained-release system on the surface of titanium dioxide nanotubes. The titanium specimens were anodized coated with HHC-36-PDLLA/PLGA. The morphology and surface elemental distribution of the specimens were evaluated. Besides, results in the present study demonstrated that with antibacterial peptide HHC-36 sustained-release coating, titanium dioxide nanotubes maintain effective drug release for 15 days in vitro, and show significant antibacterial activity. The proliferation of Staphylococcus aureus can be effectively inhibited by PDLLA/PLGA-HHC-36 coated titanium dioxide nanotube. In addition, PDLLA-HHC-36 and PLGA-HHC-36 coating was demonstrated to be biocompatible and antibacterial in vivo. These findings demonstrated that HHC-36 coated titanium nanotube could improve antibacterial potential of percutaneous implants, and indicated a novel and efficient strategy in preventing bacterial infection of percutaneous implants.